MATERNAL DEATH FROM MASSIVE BLEEDING IN CASE OF PREMATURE DETACHMENT OF THE PLACENTA - Niyazmetov, R.E.; Matyakubov, B.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The article presents a case of maternal death associated with a complete placental abruption, which was complicated by massive uterine haemorrhage, hemorrhagic shock. To determine the tanatogenesis of cases of maternal death in premature placental abruption, placental sites were studied in the region of abruption, which made it possible to determine its prescription and the sequence of development of pathological processes that led to a lethal outcome.